XML description for automata manipulations - José Alves (2010)
GUItar is a visualization software tool for various types of automata (standard, weighted, pushdown, transducers, Turing machines, etc.). It provides interactive manipulation of diagrams, comprehensive graphic style creation, multiple export/import filters, and a generic "foreign function calls" (ffc) interface with external systems. In this paper we describe GUItar's XML framework and show how it allows for extensibility, modularity and interoperability.